Orodispersible Dosage Forms with Rhinacanthin-Rich Extract as a Convenient Formulation Dedicated to Pediatric Patients - Thongtham Suksawat; Witold Brniak; Ewelina Łyszczarz; Małgorzata Wesoły; Patrycja Ciosek-Skibińska; Aleksander Mendyk (MDPI AG, 2024)
Rhinacanthins, derived from Rhinacanthus nasutus, widely used in traditional medicine, exhibit antifungal, anticancer, antiviral, antibacterial, and antiplatelet aggregation effects. Recently, their anti-diabetic activity was confirmed, which makes them an interesting natural alternative in the therapy of the early stage of diabetes mellitus. The aim of this study was to demonstrate the possibility of formulating orodispersible tablets (ODTs) and orodispersible films (ODFs) containing rhinacanthin-rich extract (RRE). Tablets with 50 mg or 100 mg of RRE were produced by direct compression. ODFs were manufactured by casting of Lycoat RS 720 or polyvinyl alcohol solution with RRE and additional excipients. The mechanical properties and disintegration times of the prepared formulations were studied. The effectiveness of taste masking was analyzed with an electronic tongue system. Six months simplified stability studies were performed in conditions complying to ICH guidelines. Appropriate friability of ODTs was achieved, despite low tensile strength (0.45-0.62 MPa). All prepared ODFs successfully met the acceptance criteria regarding Young's modulus, tensile strength, and elongation at break. The observed variations in their mechanical properties were dependent on the type and quantity of polymers and plasticizers used. Disintegration time of ODTs ranged from 38.7 s to 54.2 s, while for ODFs from 24.2 to 40 s in the pharmacopoeial apparatus. Analyses made with the electronic tongue showed the significant taste-masking effect in both formulations. The addition of sucralose as a sweetener and menthol with mint flavor as a taste-masking agent was sufficient to mask an RRE's taste in the case of ODTs and ODFs. Stability studies of ODTs packed in the PVC/Alu blisters showed a decrease in the RRE content below 90% after 6 months. However, ODFs with PVA were physicochemically stable for 6 months while being stored in Alu/Alu sachets. Our study proved for the first time the possibility of the formulation of orodispersible dosage forms with RRE, characterized by good mechanical properties, disintegration time, and appropriate taste masking.